The Influence of Thin Capitalization, Company Risk, and Company Size on Tax Avoidance - Nadianti; Asrorudin, A. (IJESS International Journal of Education and Social Science, 2025)
This research aims to examine the influence of thin capitalization, company risk and company size on tax avoidance. This research uses a quantitative approach and uses associative methods. The type of data used in this research is secondary data. The data analysis method used in this research is Panel Data Regression Analysis using the Eviews version 10 application and Microsoft Excel. The population used in this research is non-cyclical consumer companies listed on the Indonesia Stock Exchange (BEI) for the 2019-2023 period. The data collection technique in this research is a purposive sampling technique and produces 24 final company samples or 120 observation data that are processed in this research. Partially thin capitalization and company risk have no effect on tax avoidance. Meanwhile, company size influences tax avoidance. The research results show that simultaneously thin capitalization, company risk and company size influence tax avoidance.